Model Manajemen Pendidikan Islam: Telaah atas Pemikiran dan Tindakan Sosial - Ahmad Fauzi (At- Ta'lim : Jurnal Pendidikan, 2016)
The issue of Islamic education in the present context, ranging from the nature of the foundational and operational, has not been resolved. From the aspect of the foundational, many people still question whether the substance of the management of Islamic education, where lies the difference between a scientific assessment of the management of public education, this paper briefly menjelsakan of the management of Islamic education as the conceptual framework of action for someone to make changes and updates in the field of education through role individuals on the values in Islam and become a positive energy towards social action in question. Management values of Islamic education, is a product of tension between energy-spiritual and the material or the spiritual-corporeal impulse can bring significant change of the dimensions of the material on the spiritual dimension (spirit, divinity) and internalize the nature of his action social.